CCDC84 Acetylation Oscillation Regulates Centrosome Duplication by Modulating HsSAS-6 Degradation - Tianning Wang; Yuhong Zou; Ning Huang; Junlin Teng; Jianguo Chen (Cell Reports, 2019)
Summary: In animal cells, centriole number is strictly controlled in order to guarantee faithful cell division and genetic stability, but the mechanism by which the accuracy of centrosome duplication is maintained is not fully understood. Here, we show that CCDC84 constrains centriole number by modulating APC/CCdh1-mediated HsSAS-6 degradation. More importantly, CCDC84 acetylation oscillates throughout the cell cycle, and the acetylation state of CCDC84 at lysine 31 is regulated by the deacetylase SIRT1 and the acetyltransferase NAT10. Deacetylated CCDC84 is responsible for its centrosome targeting, and acetylated CCDC84 promotes HsSAS-6 ubiquitination by enhancing the binding affinity of HsSAS-6 for Cdh1. Our findings shed new light on the function of (de)acetylation in centriole number regulation as well as refine the established centrosome duplication model. : Wang et al. show that CCDC84 prevents centrosome overduplication by facilitating APC/CCdh1-mediated HsSAS-6 degradation at mitotic exit. SIRT1 and NAT10 regulate the acetylation of CCDC84 at lysine 31, and only acetylated CCDC84 promotes HsSAS-6 binding to APC/CCdh1. Keywords: centrosome duplication, CCDC84, HsSAS-6, SIRT1, NAT10, acetylation